Neff Cosmetic / Muhammad Hanif Musa ... [et al.] - Musa, Muhammad Hanif; Ridzuan, Muhammad Rifqi; Jasri, Nabihah Afina; Mat Raji, Noor Sasha Amirah; Junaidi, Batrisya Uzma (2022)
The Neff cosmetic is the business that we choose to complete this business plan. All of the members agree to continue with this business as it is actually a beauty and makeup product. The ideas of this business is actually inspired by local brand product. Most of the members are so passion and into makeup and beauty industry, so we have decided to come with our own make up product. Nowadays, people are tending to loves buy makeup and beauty stuff, so we might get a big achievement if we open up our own business. The nature of business is partnership as all of the members has contribute for this business. The industry for our business is cosmetic industry as Neff cosmetic only focus on makeup and beauty stuff for women. All of the members agree to become a partnership for Neff cosmetic as most of the members are interested in cosmetic industry. Next, the location that we have been choose to expose our business is at Johor Bahru, Johor. The date of commencement for Neff cosmetic is on 1st January 2021. There are a few factors on why we choosing this business as our group proposed business. Firstly, the demanded and trend. This is because we have make a survey among our circle that most of the women nowadays are so into beauty and makeup industry, so we take an action by open up our own business which called as Neff cosmetic. Next, the interest in makeup and beauty industry. As I mention before, most of our members are passion and interested in this industry, so by having our own kind of product, it gives us opportunities to take part in business industry as well as to become one of the most famous local brand makeup that the first choices among the customer.